Treatment modalities for claw horn lesions and their effects on locomotion scores, gait properties, lesion progression, and nociceptive threshold in dairy cows: a systematic review - Sadiq, Mohammed Babatunde; Ramanoon, Siti Zubaidah; Syed-Hussain, Sharifah Salmah; Mansor, Rozaihan; Mossadeq, Wan Mastura Shaik; Degu, Nurhusien Yimer (Elsevier BV, 2024)
This systematic review presents scientific evidence on treatment modalities for claw horn lesions (CHLs ) in dairy cows, and their efficacy in restoring normal gait, resolution of claw lesions, and improving nociceptive threshold. A literature search was performed in four databases leading to the synthesis of 10 articles for the final analysis. The types of treatment administered include single (STM), bimodal (BTM) and multimodal treatment modalities (MTM). Locomotion scores (LS) were the most reported outcome measure, followed by the resolution of claw lesion, time to lameness cure, nociceptive threshold and gait properties. Most pairwise comparisons for LS and nociceptive threshold depicted no significant difference between the various treatment groups. Meanwhile, a few pairwise comparisons in terms of resolution of claw lesion and time to lameness cure revealed that cows receiving MTM (claw trimming + hoof block + NSAID) or BTM (claw trimming + hoof block) recorded complete resolution of CHL and significantly less time to recover compared to those treated with an STM (only claw trimming). Despite the various treatment modalities used in CHL treatment, their effects on LS, nociceptive threshold, and gait properties are still unclear. While evidence suggests that MTM and BTM facilitate rapid resolution of CHL and duration of lameness cure, only limited data are available and the association with specific lesions is poorly understood. Several sources of heterogeneity were identified between the studies, particularly duration of follow -up after treatment, LS systems, severity and duration of lameness, and treatment modalities.